2019
DOI: 10.1111/jen.12651
|View full text |Cite
|
Sign up to set email alerts
|

Repellent activity of Cymbopogon citratus and Tagetes minuta and their specific volatiles against Megalurothrips sjostedti

Abstract: Cowpea is an important source of protein for people in Africa. However, the crop suffers major damage and yield losses due to bean flower thrips, Megalurothrips sjostedti Trybom (Thysanoptera: Thripidae). Although companion plants are known to reduce the damage caused by insect pests, the role of their volatiles in repelling pests from target plants has been the subject of few investigations. Here, we used the Y‐tube olfactometer experiments and chemical analyses to investigate the effect of volatiles from cow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…One of most widely recognized effects shown by plant essential oils is a repellency activity on insect pests, and this could cause a significant reduction of the target pest populations on plants. Citral, one typical kind of plant secondary metabolite and a major compound of essential oils (EOs), also exhibits repellent effects on some insect pests [ 29 ], such as Aedes aegyptis [ 12 ], Aedes albopictus [ 13 , 30 ], Rhopalosiphum padi [ 31 ], Megalurothrips sjostedti [ 32 ], and Bactrocera cucurbitae [ 33 ]. In the present study, GC film, which incorporated the bioactive essential oil citral, showed a repellency effect against BPH, as determined by the 60.00% repellency recorded.…”
Section: Discussionmentioning
confidence: 99%
“…One of most widely recognized effects shown by plant essential oils is a repellency activity on insect pests, and this could cause a significant reduction of the target pest populations on plants. Citral, one typical kind of plant secondary metabolite and a major compound of essential oils (EOs), also exhibits repellent effects on some insect pests [ 29 ], such as Aedes aegyptis [ 12 ], Aedes albopictus [ 13 , 30 ], Rhopalosiphum padi [ 31 ], Megalurothrips sjostedti [ 32 ], and Bactrocera cucurbitae [ 33 ]. In the present study, GC film, which incorporated the bioactive essential oil citral, showed a repellency effect against BPH, as determined by the 60.00% repellency recorded.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that myrcene is an aggregation synergist [ 34 ] for Monochamus alternatus (Coleoptera: Cerambycidae) [ 35 ] and Megalurothrips sjostedti (Thysanoptera: Thripidae) [ 36 , 37 ]. However, A. bungii females showed significant repulsion to 100 µL, 200 µL, and 500 µL myrcene in the semi-field cage bioassays, and 100 µL myrcene significantly reduced the number of A. bungii females choosing the host plant.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, garlic plant is repellent against the cabbage aphid, Brevicoryne brassicae L. (Hemiptera: Aphididae) (Pahla et al., 2014), red flour beetle, Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) (Mobki et al., 2014), the diamondback moth, Plutella xylostella L. (Lepidoptera: Plutellidae) (Karavina et al., 2014) and D. citri (Mann et al., 2011). Lemongrass has been successfully used as an intercrop in the management of the eggplant fruit and shoot borer, Leucinodes orbonalis Guenee (Lepidoptera: Crambidae) (Calumpang et al., 2013) and as a repellent against the larvae of the bean flower thrips, Megalurothrips sjostedti Trybom (Thysanoptera: Thripidae) (Diabate et al., 2019) and toxic to the diamondback moth, P. xylostella L. (Ohsawa, 2008).…”
Section: Introductionmentioning
confidence: 99%